Social entrepreneurship and sustainable competitive advantage: an Islamic perspective - Mhd. Sarif, Suhaimi (2010)
This study evaluates from an Islamic perspective the role of social entrepreneurship in offering sustainable competitive advantage to firms. Social entrepreneurship is an integrated concept of commercial entrepreneurship that addresses the triple bottom line (3BL), namely profit, people and planet. Thus, it provides better position for firms to outcompete the rivals on long term basis. Meeting the needs of the stakeholders’ needs (including the natural environment) is vital to ensure sustainability. This concept is in line with Islamic perspective that emphasized on Tawhidic (oneness of Allah) paradigm, the fiduciary role as servant and vicegerent of Allah, and the relationship with other creatures. The Islamic perspective also views to sustain competitive advantage through social entrepreneurship is the integration of the belief system of Islam, organizational realities, and the nature of man. Man plays a critical role in integrating Islam into organizational realities. Hence, the most apparent element that needs to be Islamized is man who is managing, coordinating, and making the objectives a successful reality. The Qur’an has outlined ways and means of managing competitiveness that established justice, fairness and harmony.